2010
DOI: 10.1093/humupd/dmq022
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraception and risk of cancer

Abstract: Women wishing to use combined OC can be reassured that their decision is unlikely to place them at higher risk of developing cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
0
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(139 citation statements)
references
References 178 publications
2
119
0
18
Order By: Relevance
“…Other epidemiologic characteristics do not differ significantly between BOT and ovarian carcinomas, and epidemiological studies have also confirmed similar reproductive risk factors in BOTs as in ovarian cancers, except for higher frequency of infertility [18,19]. Rather than a single hypothesis, an overlap in mechanisms involved in each hypothesis may more likely explain the reproductive risk factors in full.…”
Section: Epidemiologymentioning
confidence: 98%
“…Other epidemiologic characteristics do not differ significantly between BOT and ovarian carcinomas, and epidemiological studies have also confirmed similar reproductive risk factors in BOTs as in ovarian cancers, except for higher frequency of infertility [18,19]. Rather than a single hypothesis, an overlap in mechanisms involved in each hypothesis may more likely explain the reproductive risk factors in full.…”
Section: Epidemiologymentioning
confidence: 98%
“…OCPs have protective effects due to the efficacy of progesteronic agents against endometrial cancer. At least one year of OCP use is associated with a 50% decline in the risk of cancer; this protection is maximized by 3 years of OCP use (the effects persist for 20 -30 years) (23). The protective properties of OCPs affect 3 types of endometrial cancers, ie, endometrioid carcinoma, clear cell endometrial cancer, and papillary serous endometrial cancer (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that contraceptives have a significantly protective effect on carcinoma of ovary and corpus uteri. 19,20 In fact, a collaborative reanalysis of individual data from 53 297 women with breast cancer and 100 239 women without breast cancer from 54 epidemiological studies revealed that while women were taking COC pills and in the 10 years after stopping, there was a small increase in the relative risk of breast cancer. 21 There was, however, no significant excess risk of having breast cancer diagnosed ≥10 years after stopping use of COC pills.…”
Section: Discussionmentioning
confidence: 99%